Effect of meconium ileus on the clinical prognosis of patients with cystic fibrosis - Oliveira,M.C.L.A. (2002)
The objective of the present study was to determine the possible prognostic factors which may explain the difference in the survival of patients with cystic fibrosis (CF) with and without meconium ileus. Over a period of 20 years, 127 patients with CF, whose diagnosis was confirmed by typical clinical characteristics and altered sweat chloride levels, were studied retrospectively. The patients were divided into two groups: group 1 consisted of patients who presented CF and meconium ileus (N = 9), and group 2 consisted of patients with CF without meconium ileus (N = 118). The characteristics studied were based on data obtained upon admission of the patients using a specific protocol. Demographic, clinical, nutritional and laboratory data were obtained. The genotype was determined in 106 patients by PCR. Survival was analyzed using the Kaplan-Meier method. The median follow-up period was 44 months. A statistically significant difference was observed between the groups studied regarding the following variables: age at diagnosis and weight and height z scores. The presence of meconium ileus was associated with an earlier diagnosis; these patients had greater deficits in height and weight at the time of diagnosis and at the end of the study. The estimated probability of survival for patients with CF without meconium ileus was 62 ± 14% and for those with meconium ileus 32 ± 18%. Patients with CF and meconium ileus presented a poor nutritional status at diagnosis and a lower survival rate compared to the general CF population.